Wireless power transfer system for electric vehicle application - Mohamed Firdaus Bin Mohamed Iqbal (2023)
This thesis highlights on identifying the parameters affecting the transmission efficiency and methods to abuse the parameter to achieve high transmission efficiency. This thesis also identifies the most suitable type of WPT technology to be used in the charging process of EV. Fundamental equation in modelling a wireless power transmission system via strongly coupled magnetic resonance such as the circuit model of the system, resonance model, coupled model and the resonant frequency is listed in the thesis. CST Microwave Studio is used in investigating the parameter affecting the transmission efficiency in designing the coiling system. The parameter that will be investigated are coupling strength by varying the distance between coil, variation in the number of turns and distance varying to archive critical coupling.